2017
DOI: 10.1038/srep46021
|View full text |Cite
|
Sign up to set email alerts
|

FKBP65-dependent peptidyl-prolyl isomerase activity potentiates the lysyl hydroxylase 2-driven collagen cross-link switch

Abstract: Bruck Syndrome is a connective tissue disease associated with inactivating mutations in lysyl hydroxylase 2 (LH2/PLOD2) or FK506 binding protein 65 (FKBP65/FKBP10). However, the functional relationship between LH2 and FKBP65 remains unclear. Here, we postulated that peptidyl prolyl isomerase (PPIase) activity of FKBP65 positively modulates LH2 enzymatic activity and is critical for the formation of hydroxylysine-aldehyde derived intermolecular collagen cross-links (HLCCs). To test this hypothesis, we analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…In the intracellular molecular binding assay (Fluoppi assay), PLOD2 and integrin b1 formed complex at the ER (ER) as shown in Figures 3B, 3C, and S6, then the integrin b1 moved to filopodia and the plasma membrane (Figure 3D). ER localization of PLOD2 has been reported in the previous studies (Chen et al, 2017;Gjaltema et al, 2016), which is consistent with our present result, indicating that PLOD2 first hydroxylizes integrin b1 at the ER, following which the integrin b1 is recruited to the cell surface functional site after the modification.…”
Section: Discussionsupporting
confidence: 94%
“…In the intracellular molecular binding assay (Fluoppi assay), PLOD2 and integrin b1 formed complex at the ER (ER) as shown in Figures 3B, 3C, and S6, then the integrin b1 moved to filopodia and the plasma membrane (Figure 3D). ER localization of PLOD2 has been reported in the previous studies (Chen et al, 2017;Gjaltema et al, 2016), which is consistent with our present result, indicating that PLOD2 first hydroxylizes integrin b1 at the ER, following which the integrin b1 is recruited to the cell surface functional site after the modification.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, Hsp47 was recently identified as an anchor molecule between collagens and TANGO1 at ER exit sites (37), and this interaction plays a crucial role for loading collagens into special COPII vesicles for secretion. FKBP65 was also proposed to associate with lysyl hydroxylases and CypB inside the cell (51,58,59); however, no binding affinities were determined in these studies. These observations suggest that the weak interaction between Hsp47 and FKBP65 reflects their multifunctional roles through binding to other protein components of the molecular ensemble for collagen biosynthesis in the rER.…”
Section: The Role Of the Binding Of Hsp47 To Fkbp65 In The Rermentioning
confidence: 93%
“…The major glycosylation in type I collagen occurs at the helical cross-linking sites near the N-terminus, and it may regulate cross-link maturation (72)(73)(74)(75). Recent studies showed that LHs are regulated by a number of ER-resident chaperones and foldases (76)(77)(78)(79)(80)(81)(82). Defects in these LH-associated proteins result in abnormal collagen cross-links that lead to bone and connective tissue disorders (81,83,84).…”
Section: Fibrosis and Intratumoral Immune Surveillancementioning
confidence: 99%
“…Minoxidil has been used to inhibit LH2 in preclinical models (180), but its mode of action is unclear. LH2 might also be targeted indirectly with tacrolimus, which inhibits FKBP65, a peptidyl prolyl isomerase that enhances LH2 enzymatic activity (79,80). Developing selective inhibitors of collagen-modifying enzymes will require insight into the structural properties of their active sites, but crystal structures of these enzymes have not been reported.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%